Identification of cellular targets of microRNA-181a in HepG2 cells: a new approach for functional analysis of microRNAs - Tan, Jane Yi Lin (2015)
MicroRNAs (miRNAs) are known to play a part in regulating important cellular processes. They generally perform their regulatory function through their binding with mRNAs, ultimately leading to a repression of target protein expression levels. However, their roles in cellular processes are poorly understood due to the limited understanding of their specific cellular targets. Aberrant levels of miRNAs have been found in hepatocellular carcinoma (HCC) including miR-181a. Using bioinformatics analysis, cyclin-dependent kinase inhibitor 1B (CDKN1β) and transcriptional factor E2F7 were identified as potential targets of miR-181a. Validation analysis using surface plasmon resonance (SPR) showed a positive binding between miR-181a and the 3’UTRs of these two potential mRNA targets. In vivo luciferase assay further confirmed the positive miR-181a:mRNA bindings, where a significant decrease in luciferase activity was detected when HepG2 cells were co-transfected with the 3’UTR-containing reporter plasmids and miR-181a. The potential impact of miR-181a binding to its specific targets on the general cellular behavior was further investigated. Results showed that miR-181a significantly activated the MAPK/JNK pathway which regulates cell proliferation, supporting our recently reported findings. Inhibition of miR-181a, on the other hand, abolished the observed activation. Our findings open up a new approach in designing targeted functional analysis of miRNAs in cellular processes, through the identification of their cellular targets.